Intestinal mucoadhesive devices for oral delivery of insulin. Issue 3 (19th August 2016) - Banerjee, Amrita; Lee, JooHee; Mitragotri, Samir
Abstract: Oral delivery of proteins such as insulin has been a long‐lasting challenge owing to gastrointestinal degradation and poor permeability of therapeutic macromolecules across biological membranes. We have developed mucoadhesive intestinal devices for oral delivery of insulin to address this challenge. Here we demonstrate a combination of intestinal devices and a permeation enhancer, dimethyl palmitoyl ammonio propanesulfonate (PPS), for oral delivery of insulin. The devices were delivered from a capsule coated with a pH‐responsive enteric coating. The devices adhere to intestinal mucosa, release their protein load unidirectionally, and prevent enzymatic degradation in the gut. Devices were found to completely release their drug load within 3–4 hr and showed excellent strength of mucoadhesion to porcine intestine. Devices loaded with insulin and PPS significantly decreased blood glucose levels by 30 and 33% in diabetic and nondiabetic rats, respectively. These studies demonstrate that intestinal mucoadhesive devices are a promising oral alternative to insulin injections and therefore should be further explored for the treatment of diabetes. Abstract : This study describes a novel method for oral delivery of insulin using intestinal patches.